Communicative toolkit of virtual reality in modern design practice and its impact on participatory practices (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
This study examines the impact of virtual reality (VR) as a communicative tool in architectural design, specifically in the stages of analysis, modeling, and designing architectural environments. The global and Ukrainian experiences of using VR in the project process are compared, with a focus on participatory practices involving active engagement from the public and other stakeholders. The study explores how virtual technologies change the interaction between project participants and open up new opportunities for the future development of these practices.The research analyzes successful case studies where VR has become an effective tool for improving communication and decision-making, comparing it to traditional methods of public engagement. Special attention is given to the influence of virtual technologies on the architecture profession, as well as the changes occurring in the processes of design and communication.A key feature of the publication is the development of a model that systematizes the experience of using VR in architectural practice and identifies the potential of VR to optimize interaction between project participants at different stages of design. The study offers new approaches to forming participatory practices in the context of digital technologies and outlines the main advantages and challenges that may arise when integrating them into architectural practice.Virtual technologies have immense potential to enhance communication and improve interaction with the community. They not only allow visualizing the final result but also modeling potential development scenarios of the urban environment, assessing risks, and evaluating possible consequences for the environment, society, and the economy. According to recent research, VR contributes to accelerating decision-making processes in public discussions by enabling the demonstration of different project options and obtaining real-time feedback, which improves the accuracy and speed of decision-making.Thus, virtual technologies hold significant potential for improving participatory practices, providing more interactive, realistic, and effective interaction between all participants in the design process. However, for their widespread implementation, it is necessary to overcome technical and organizational barriers that limit their use. Further research will help not only refine tools for participatory design but also expand educational programs by integrating VR as a core tool for modeling, analysis, and designing architectural environments.
Keywords: virtual reality; architectural design; participatory practices; communication; interactive technologies